POLA PENGELOLAAN SEKOLAH BARU; STUDI KASUS DI KB (KELOMPOK BERMAIN) SYIFA AZZAHRA - Utama, Yudi Nanda (Program Studi Manajemen Pendidikan Islam, 2024)
Equity in education must be realized in its implementation. In Sirambas Village, the distribution of Early Childhood Education (KB) programs remains uneven, and many community members are reluctant to enroll their children in KB, considering it unimportant and costly. This study employs a qualitative approach with a case study method. Data were collected through interviews, observations, and document analysis, then analyzed using data reduction, data presentation, and conclusion drawing. The findings at KB Syifa Azzahra in Sirambas Village reveal: (1) school management is based on the philosophy